Surgeon Involvement in Pre-Clinical Medical Education: Attitudes of Directors of Education - Turner, Simon; Diederichs, Brendan; de Gara, Christopher (Canadian Medical Education Journal, 2012)
Background: Application rates to surgical residencies have shown a downward trend recently. Introducing students to surgeons early in medical school can increase interest in surgery as a career and enhance the instruction of important surgical topics. Directors of undergraduate medical education have unique insight and influence regarding the participation of surgeons in pre-clinical education. Methods: To understand the attitudes of these educators towards surgeons as teachers in pre-clinical programs, a survey was administered to the directors of undergraduate medical education at each of the English-language medical schools in Canada. Results: Educators estimate the participation of surgeons in all categories of pre-clinical education to be low, despite being valuable, and think that it should be increased. The most significant barrier to participation identified was a lack of surgeons’ time. Conclusions: Despite the value of surgeons participating in pre-clinical education, their rate of participation is low. Steps should be taken to facilitate the involvement of surgeons in this phase of education, which may lead to improved education for students and increased student interest in surgery residencies.